Reporting Obligations for Infectious Diseases and Patient Confidentiality in Health Law - Agustina, Lina; Vitrianingsih, Yeni; Issalillah, Fayola (Metromedia, 2025)
The law on healthcare workers' duty to report infectious diseases in Indonesia is based on Law No. 17 of 2023 on Health and implementing regulations governing the surveillance system. On the one hand, reporting is required as a tool to prevent and control the spread of diseases that threaten the wider public. On the other hand, the principles of patient confidentiality and personal data protection require that medical information be protected from unauthorized access and use. This article uses a normative juridical approach with qualitative literature study to examine the relationship between reporting obligations and patient privacy rights. Primary legal materials in the form of laws and regulations in the fields of health, medical records, and personal data protection are analyzed together with literature on public health ethics and contemporary bioethics. The results of the analysis show that the reporting obligation is constructed as an imperative public norm, while the confidentiality of medical records and patient personal data is positioned as a private norm that protects the dignity and integrity of individuals. The two are harmonized through clear exceptions, restrictions on the use of data, and the obligation to implement procedures that maintain patient anonymity in the public sphere. This article concludes that national regulations, including the Health Law, implementing regulations, the Minister of Health Regulation on Medical Records, and the Personal Data Protection Law, have normatively provided a legal framework that is relatively balanced between public health interests and patient privacy rights. Operational guidelines and data governance at the health facility level need to be strengthened so that reporting obligations are carried out in accordance with confidentiality protection standards and public health ethics principles.